Assessment of the impact of lifestyle and psychosocial working conditions on older employees' work ability. Issue 3 (3rd July 2021) - Malińska, Marzena; Bugajska, Joanna
Abstract : Objective. The purpose of this article was to assess the impact of selected elements of lifestyle, psychosocial working conditions and general mental health on older employees' ability to work. Methods . Employees ( N = 1067) aged 50–65 years ( M 54.8, SD 3.95) responded to a questionnaire on demographics, lifestyle characteristics, general mental health (general health questionnaire), psychosocial job characteristics (job content questionnaire) and work ability (work ability index [WAI]). A logistic regression model was used to assess the impact of the selected factors on work ability. Results. Older employees were characterized by good (44.4%) and moderate (36.4%) work ability. The average WAI scores were significantly higher among employees who did not smoke, consumed the recommended daily intake of vegetables, drank enough water, ate breakfast every morning, cut down on sweets and were on a vegetarian diet. Good physical (no sick leave) and mental health, high level of job control, low job insecurity and use of over-the-counter drugs were found to be the strongest predictors of WAI scores. Conclusions . The results of the research indicate that most of the determinants of work ability identified at work are impacted, thus giving the opportunity to conduct some occupational health and preventive programmes in the workplace.